Evaluation of Sleep Disorders in the Elderly with Vestibular Vertigo - Zahra Hosseini Dastgerdi; Nasrin Gohari; Mobina Mehrabifard; Hasti Seifi; Bahare Khavarghazalani (Journal of Health Sciences and Surveillance System)
Background: Vestibular vertigo and decreased sleep quality are prevalent issues that significantly affect the life expectancy, quality of life, and mental health of the elderly. Evidence from human and animal studies suggests a link between sleep disorders and vertigo. However, this association has not been sufficiently explored in the elderly population. The present study investigates the associations between vertigo-induced handicap and sleep quality in older people.Methods: This cross-sectional study included individuals aged 60–70 with vestibular vertigo. The participants completed two questionnaires—the Dizziness Handicap Inventory (DHI) and the Pittsburgh Sleep Quality Index (PSQI)—in the presence of one of the authors.Results: In this study, 96% of participants exhibited some degree of poor sleep quality. Correlation analysis revealed positive relationships between PSQI subcategory scores and specific domains of the DHI. Subjective sleep quality was significantly associated with DHI-Total (DHI-T), DHI-Emotional (DHI-E), and DHI-Functional (DHI-F) scores. Sleep disturbance showed significant links with the DHI-E and DHI-F domains. The use of sleeping medication was significantly correlated with DHI-T, DHI-E, and DHI-F scores, while daytime dysfunction was associated with DHI-T and DHI-F scores (P<0.05). However, the PSQI-Total (PSQI-T) score did not show significant correlations with DHI-T, DHI-P (Physical), DHI-E, or DHI-F scores (P>0.05).Conclusion: This study demonstrated that, in elderly individuals with vestibular vertigo, there is a correlation between the degree of vertigo-induced handicap and various dimensions of sleep quality. Specifically, as the handicap worsens, sleep quality deteriorates. These findings underscore the importance of assessing sleep quality when evaluating elderly patients with vestibular vertigo.